SISTEM INFORMASI PENGOLAHAN NILAI SISWA BERBASIS WEB PADA SMP PANMAS DEPOK - Jamil Satrio Pinanggito (2023)
The student assessment system at Panmas Depok Junior High School still uses the manual method, namely the teacher processes data manually by means of paper media and Microsoft Excel. Such a method is the main factor for errors in data input, including calculating wrong values, if any data is input incorrectly it must be changed one by one, and also errors when placing data. Therefore, the author designed a website-based application called "Value Information System" to solve this problem where in this system, users are divided into 3, namely teachers who input student grades data and learning schedules, admins who process grades and student biodata, and students who can see which class they are following. This system was created with the aim of making it easier for teachers and admins to process data. In making the system, the author uses the Waterfall method and uses the Laravel Framework with PHP language.